Encouraging ecopreneurship through lifelong education: A qualitative constructivist grounded theory study - Potluri, Seema; Phani, B. V. (International Review of Education, 2024)
Over the past decade or so, international agencies and scholarly research have identified "ecopreneurship" as one of the key mechanisms to synchronously equalise the pace of economic, environmental and social development across countries. However, progres
Keywords: Ecopreneurship; Environment; Green Entrepreneurship; Lifelong Education; Lifelong Learning